ETHEREUM BLOCKCHAIN TECHNOLOGY FOR INTERNET OF THINGS AUTHENTICATION - HASSAN, NOOR SALAH; AL-KHALIL, AHMAD B. (Journal of Duhok University, 2023)
The Internet of Things (IoT) technology has grown rapidly and continuously. The IoT ecosystem comprises an increasing number of smart devices that can sense, act, process, store, and communicate via the Internet. Data within such communication technology is continuously exposed to be hacked or attacked. Therefore, there should be methods to protect the issue of data authentication and increase the security of such large-scale networks. In this article, a method of using a Blockchain network is proposed. The proposed system uses the Ethereum blockchain and benefits from several critical technologies, including distributed consensus, smart contracts, digital signatures, and cryptographic hashes. The whitelist and blacklist are the two lists that are suggested. The approved users who have obtained their private keys are included on the whitelist. The blacklist, on the other hand, is intended to stop illegal users who are flagged as spammers or attacks. According to findings, the Blockchain can drastically save expenses and boost the security of IoT networks